2021
DOI: 10.3390/molecules27010115
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening by LC-ESI-MS/MS and Effect of the Ethyl Acetate Fraction from Leaves and Stems of Jatropha macrantha Müll Arg. on Ketamine-Induced Erectile Dysfunction in Rats

Abstract: Jatropha macrantha Müll Arg. L is also known as “huanarpo macho” and used in the Peruvian traditional medicine as an aphrodisiac and erectile dysfunction (ED). The aim of this study was to determine the phytochemical constituents in leaves and stems ethyl acetate fraction (LEAF and SEAF) of J. macrantha and to compare the antioxidant activity and the ameliorative effect on ketamine-induced erectile dysfunction in rats. The phytochemical constituents were determined by LC-ESI-MS/MS, the total phenolic compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Studies have indicated the presence of flavonoids, alkaloids, coumarins and lignins in J. gossypiifolia and J. curcas [ 39 , 40 ]. Other studies have shown the presence of flavonoids, polyphenols, saponins and condensed tannins in the extract of J. curcas leaves [ 41 ], and flavonoids and polyphenols in the ethyl acetate fraction of leaves and roots of J. macranta [ 42 ]. Other authors have also reported similar results [ 43 , 44 , 45 , 46 ], indicating that they align with the results found here.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have indicated the presence of flavonoids, alkaloids, coumarins and lignins in J. gossypiifolia and J. curcas [ 39 , 40 ]. Other studies have shown the presence of flavonoids, polyphenols, saponins and condensed tannins in the extract of J. curcas leaves [ 41 ], and flavonoids and polyphenols in the ethyl acetate fraction of leaves and roots of J. macranta [ 42 ]. Other authors have also reported similar results [ 43 , 44 , 45 , 46 ], indicating that they align with the results found here.…”
Section: Resultsmentioning
confidence: 99%
“…In their results, the acetate fraction showed the highest concentrations, with 685 μg·mg −1 for phenols, 25.90 μg·mg −1 for flavonoids and 15.63 μg·mg −1 for tannins. Tinco-Jayo et al [ 42 ] estimated the concentration of phenolics in the range of 359 and 306 mg·g -1 and flavonoids in the range of 101–23.7 mg·g −1 in the ethyl acetate fraction of J. macrantha leaves.…”
Section: Resultsmentioning
confidence: 99%
“…It indicated that V. pinnata Linn leaves have a wide range of semi-polar compounds, such as polyphenolic compounds of flavonoids [37][38]. High contents of phenolic content in the ethyl acetate fractions were also reported by Shafie et al [39] working with Vitex pinnata leaves (33.1 ± 0.1 mg QE/g), de Brum et al [40] working with Vitex megapotamica leaves (522.4 ± 1.12 mg GAE/g), Gothai et al [41] with Moringa oleifera leaves (65.81 ± 0.01 mg GAE/g ), Lasboi et al [42] with Muntingia calabura L leaves (74.90 mg GAE/g), Okselni et al [43] with Elaeocarpus mastersii Kings roots, leaves, and stem bark (362.88 ± 1.89 mg GAE/g, 380.99 ± 2.14 mg GAE/g, and 341.89 ± 3.97 mg GAE/g ), and studies Tinco-Jayo et al [44] with Jatropha macrantha Müll Arg. L leaves and stems (359 ± 5.21 mg GAE/g and 306 ± 1.93 mg GAE/g).…”
Section: Extractionmentioning
confidence: 96%
“…Phytochemical analyses have identified polyphenolic compounds such as coumaric acid and ferulic acid as biologically active compounds in A. distichum (Kim and Lee, 2015;Choi et al, 2017;Yoo et al, 2021). In addition, positive and strong correlations between the polyphenolic contents of EtOAc fractions and their pharmaceutical activities have been reported in various plant extracts (Kim et al, 2014;Tinco-Jayo et al, 2021;Loh et al, 2022). Therefore, we hypothesized that MeJA improves the production of polyphenolic compounds, resulting in enhanced antiinflammatory effects of AdAR.…”
Section: Effect Of Etoac/meja On the Mitogenactivated Protein Kinase ...mentioning
confidence: 96%